Transport of nitrogen dioxide (NO2) and particulate matter (PM) into a mechanically ventilated office building adjacent to a busy road - Mohd Aris, Mohd Shukri; Kelly, Frank; Barratt, Benjamin (2011)
Long term indoor and outdoor monitoring of NO2 at a congested street canyon location identified high indoor concentrations prompting occupational health concerns. Indoor monitoring of different PM size fractions has been undertaken to investigate differences between gaseous and particulate transport. Characterization of monitoring results has revealed a number of important building design issues relating to the transport of pollution into a mechanically ventilated building. The building managers have agreed a series of improvements, the impact of which will be monitored over the coming months.